Highly versatile immunostimulating nanocapsules for specific immune potentiation. (2014) - Vicente, Sara; Peleteiro, Mercedes; Gonzalez-Aramundiz, Jose V; Díaz-Freitas, Belén; Martínez-Pulgarín, Susana; Neissa, Jose I; Escribano, Jose M; Sanchez, Alejandro; González-Fernández, África; Alonso, Maria J
Aim: To develop a new core-shell type (nanocapsules) adjuvant system composed of squalene and polyglucosamine (PG) and to evaluate its immunostimulant capacity.Results: The defined PG nanocapsules exhibited the capacity to efficiently associate the selected antigens (recombinant hepatitis B surface antigen and hemagglutinin of influenza virus) onto their polymeric surface (70–75%), and the immunostimulant imiquimod within the oily core. The resulting nanovaccines, with a particle size of 200–250 nm and a positive zeta-potential (∼+60 mV), were able to significantly potentiate and modulate the immune response to the selected antigens upon intramuscular administration to mice. Their efficacy as novel adjuvants was attributed to their enhanced cell internalization and effective intracellular imiquimod/antigen delivery, together with their prolonged residence time at the injection site.Conclusion: The nanocapsules described herein have the capacity to enhance, prolong and modulate the immune response of subunit antigens and, therefore, they could be proposed as a platform for the codelivery of different antigens and immunostimulators. Original submitted 13 June 2013; Revised submitted 28 November 2013